Huertos escolares orgánicos como recursos didácticos en los alumnos de la escuela de educación básica general Quisquís, cantón Quevedo, periodo 2021- 2022 - Maruri Pacheco, Wesley Kazajia (2022)
The guide teacher, propitiator of natural learning, must promote environmental education based on experiences. The present research work framed in the constructivist model has as its objective: Teacher training plan: Organic school gardens as didactic resources in the students of the third General Quisquís School of Basic Education, Quevedo Canton, Los Ríos province, during the period 2022. The systematic research to be used is a qualitative approach framed in descriptive research, applying observation techniques and a survey. The results when executing the Training Plan will allow the student to strengthen concepts, values, participation, and raise awareness about the importance of improving food education using methodologies such as I learn by keeping commitment to the environment